Application of global trigger tool to determine the prevalence of adverse drug reactions in adult patients admitted to general and COVID-19 intensive care units - de Souza, Rafael Nogueira; Visacri, Marília Berlofa; Trotta, Fabiana Bragança Albanese; Ventura, Deise de Souza; Perroud, Mauricio Wesley; Moriel, Patrícia (Frontiers in Pharmacology, 2025)
ObjectiveThe primary aim of this study was to determine the prevalence of adverse drug reactions (ADRs) in adult patients admitted to a general adult intensive care unit (G-ICU) and a COVID-19 adult intensive care unit (C19-ICU). The secondary aims were to characterize patients in both ICUs; identify factors associated with the occurrence of ADRs; assess the performance of triggers in detecting ADRs; describe ADRs in terms of severity, mechanism, causality, and suspected drugs; and compare the trigger tool methodology with spontaneous reporting.MethodsThis was a descriptive and retrospective study involving the application of triggers adapted from the Global Trigger Tool to identify ADRs through the analysis of physical and electronic medical records, medical prescriptions, and laboratory test results of adult patients admitted to the G-ICU and C19-ICU of a tertiary hospital in Sumaré (HES), São Paulo, Brazil, from January 2020 to December 2020. The patients were characterized by sex, age, length of stay, clinical outcome (discharge or death), and sequential organ failure assessment (SOFA) scores. The performance of triggers in detecting ADRs was determined by calculating positive predictive value (PPV). ADRs were characterized by severity, mechanism, causality, and suspected drugs. The 2020 spontaneous reporting database at the HES was analyzed, and ADRs from the ICUs were identified.ResultsThe study evaluated 135 patients (56.3% from the G-ICU and 43.7% from the C19-ICU), with a predominance of males (54.8%) and a mean age of 61.0 ± 15.1 years. The mean hospital stay was 13.0 ± 11.0 days, the average SOFA score throughout hospitalization was 8.4 ± 3.8, and the ICU mortality rate was 69.6%. Of the 135 admitted patients, 55 (40.7%) presented with at least one ADR, of which 31 (52.5%) were admitted to the C19-ICU. The length of hospitalization was associated with the presence of ADR in both ICUs studied and age only in the C19-ICU. Additionally, patients admitted to the C19-ICU had a 2.4 times higher risk of developing ADRs. A total of 85 ADRs were identified, 65 (76.5%) of which occurred through triggers. The triggers with the best performance in detecting ADRs, with a PPV of 100%, were “Partial Thromboplastin Time >50,” “Skin Rash,” “Protamine,” and “Hydroxyzine.” Most ADRs were moderate (56.5%), Type A (96.5%), and classified as possible (64.7%). Insulin was the drug most frequently associated with ADRs, with 22 occurrences. Only five ADRs in ICU patients were spontaneously reported in 2020.ConclusionOf all the patients, 40.7% experienced at least one ADR during hospitalization. The number of ADRs identified by the trigger tool was significantly higher than those reported spontaneously. This demonstrates that using triggers to investigate ADRs is an effective method to significantly enhance an institution’s pharmacovigilance actions.